ORGANIZATIONAL CITIZENSHIP BEHAVIOR DALAM KAJIAN FILSAFAT ILMU - Harsono, Mugi - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2004)
ABSTRACT Â  The tendency of science cutting loose from its philosophy, causing science loss its vision and philosophical orientation. On that account, effort to bring into contact to return the science with its philosophy root represents actual agenda for academic world. The purpose of this article is discussing the philosophical aspects of Organizational Citizenship Behavior, a relative newly construct in Organizational Behavior. The study is conducted based-on three science philosophy pillars, namely ontology, epistemology and axiology. The result indicates that from aspect ontological, epistemological and also axiological, OCB represent study object having a significance contribution to Organizational Behavior studies. Keywords: Philosophy of Science; Organizational Citizenship Behavior; Ontology; Epistemology; Axiology